Light-activated nanomaterials for tumor immunotherapy - Wang, Fang; Duan, Huijuan; Xu, Weizhe; Sheng, Gang; Sun, Zhaogang; Chu, Hongqian (Frontiers in Chemistry, 2022)
Tumor immunotherapy mainly relies on activating the immune system to achieve antitumor treatment. However, the present tumor immunotherapy used in the clinic showed low treatment efficacy with high systematic toxicity. To overcome the shortcomings of traditional drugs for immunotherapy, a series of antitumor immunotherapies based on nanomaterials have been developed to enhance the body's antitumor immune response and reduce systematic toxicity. Due to the noninvasiveness, remote controllability, and high temporal and spatial resolution of light, photocontrolled nanomaterials irradiated by excitation light has been widely used in drug delivery and photocontrolled switching. This review aims to highlight recent advances in antitumor immunotherapy based on photocontrolled nanomaterials. We emphasized the advantages of nanocomposites for antitumor immunotherapy and highlighted the latest progress of antitumor immunotherapy based on photoactivated nanomaterials. Finally, the challenges and future prospects of light-controlled nanomaterials in antitumor immunity are discussed.